Combating Hoaxes in Elections: The Role of High School Education in Safeguarding Democracy - Hildawati; Pratiwi, Angelika Yuni; Two, Abril Tika Gagas; Julisa, Monika; Firmansyah, Yoki (Papanda Publishier, 2025)
The proliferation of hoaxes in Indonesia, particularly during election periods, poses significant challenges to the nation's democratic process by influencing public perception, destabilizing socio-political conditions, and undermining trust in institutions. This study explores the understanding and involvement of high school students in detecting hoaxes and monitoring information. Conducted at SMA Taruna Bumi Khatulistiwa Pontianak, the research utilized a qualitative descriptive method, involving 115 students who participated in the program